Likembe tunings of Kufuna Kandonga (Angola) - Kubik, Gerhard (International Library of African Music, 1980)
The object of the present article is an analysis of the likembe tunings of one Angolan musician, Kufuna Kandonga, on the basis of his tuning process, his musical terms and the results of the measurements of his tunings. All this is related to the wider context of Ngangela/Mbwela musical concepts and the history of the likembe in Central Africa. His tuning process was observed by me over a period of six weeks while we travelled together in southeastern Angola in 1965, and he carried his likembe with him.
Keywords: African Music; Angola